2015
DOI: 10.3329/bjmed.v26i1.25649
|View full text |Cite
|
Sign up to set email alerts
|

Use of Blood and Blood Components In Dhaka Medical College Hospital

Abstract: Introduction: Use of blood means providing the right blood product, in the right quantity, for the right patient. It can help in bridging the gap between demand and supply of the precious blood or blood products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…A total of 10184 blood components were prepared during the year 2017. Maximum number of blood units were collected in October which is 10 9.6 times more blood components were used compared to Whole Blood utilization and this ensures effective utilisation of blood and its components. Only 4 units of Cryoprecipitate (0.04%) were utilized in the month of December.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 10184 blood components were prepared during the year 2017. Maximum number of blood units were collected in October which is 10 9.6 times more blood components were used compared to Whole Blood utilization and this ensures effective utilisation of blood and its components. Only 4 units of Cryoprecipitate (0.04%) were utilized in the month of December.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Studies have revealed high proportion of inappropriate use of blood transfusion often in both developed and developing countries. [8,10] This study aims to evaluate the prevalence of TTI in donors in blood bank of Institute of Social Obstetrics and Government Kasturba Gandhi Hospital for Women and Children, Triplicane, Chennai, India over a period of one year. This study also aims at evaluating the pattern of utilization of blood and components in a tertiary care hospital, tries to bring down the excess usage and discard of blood and components.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%
“…Blood transfusion was first performed successfully by James Blundell in 1818 [1]. Blood component therapy has gained much of the interest in recent years because of its merits over whole blood transfusion like, it reduces volume overload on patient and has greater shelf life, better patient management [7]. Component therapy was introduced between 1950 and 1960s [7] to maximize the benefits of all components present in the whole blood [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…As blood is a scarce resource, clinician should weigh the risks of transfusion against risks of not transfusing [5]. Data on the use of blood products are limited, studies have revealed high proportion of inappropriate use of blood transfusion often in both developed and developing countries [6,7]. Evaluation of pattern of blood component usage, its demand and good audit management is needed to ensure appropriate utilization of precious resource.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation